1985
DOI: 10.3109/17453678508992995
|View full text |Cite
|
Sign up to set email alerts
|

Intracapsular pressure in transient synovitis of the hip

Abstract: Fourteen consecutive children with symptoms of transient synovitis of the hip were examined with sonography regarding intracapsular effusion, with scintimetry regarding blood-flow in the proximal femoral epiphysis (PFE) and with intracapsular pressure recording and aspiration. All patients had an intracapsular effusion. Intracapsular pressure was found to depend on the position of the hip. The mean pressure with hips in extension and inward rotation was 22.6 kPa (170 mm Hg) whereas in 45 degrees of flexion it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
6

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 11 publications
0
19
1
6
Order By: Relevance
“…We postulate that there is a relation between the decreased signal intensity with enhancement at the femoral epiphysis that we observed and perfusion of the femoral head. Kesteris et al [29] and Wingstrand et al [30] reported the significance of increased intracapsular pressure related to hip joint effusion in patients with transient synovitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We postulate that there is a relation between the decreased signal intensity with enhancement at the femoral epiphysis that we observed and perfusion of the femoral head. Kesteris et al [29] and Wingstrand et al [30] reported the significance of increased intracapsular pressure related to hip joint effusion in patients with transient synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend performing MRI before arthrocentesis in patients with irritable hip because reports [21,29,30] suggest that intracapsular pressure, effusion, and impaired perfusion of the hip are related to one another. Caird et al [18] and Luhmann et al [2] isolated various organisms from cultures of patients with confirmed septic arthritis of the hip.…”
Section: Discussionmentioning
confidence: 99%
“…The tension of the hip capsule is increased in extension and internal rotation and especially in hips with effusion (Wingstrand et al 1985b) -a condition that may result in an altered distribution of the fluid within the joint. This may exaplain the slight discrepancy between US and CT measurements obtained in those hips with the largest effusion, because the reproducibility of hip flexion and rotation between the two examinations was less accurate in the patients with the most pain.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally and clinically increased intracapsular pressures have been shown to produce ischemia of the proximal femoral ephiphysis (Woodhouse 1964, Lucht et al 1983, Kloiber et al 1983, Wingstrand et al 1985b.…”
Section: Discussionmentioning
confidence: 99%
“…A two-plane image intensifier was used. The joint capsule was punctured with a 1.2 mm epidural needle connected via a tube with heparinized saline to a piezoelectric pressure transducer (Wingstrand et al 1985). The joint pressure was recorded immediately after puncture of the joint in neutral extension, in maximal inward and outward rotation in extension, and at 45 degrees of neutral flexion.…”
Section: Methodsmentioning
confidence: 99%